Epêntese vocálica medial: análise dos efeitos da segunda língua (l2) na produção de língua materna (l1) sob a ótica da sociolinguística variacionista - Lima, Luana Anastácia Santos de (2018)
This thesis aims to investigate the effects of L2 acquisition by bilingual speakers on L1 processing, through the variational analysis of the epenthetic vowel in word medial clusters, as in apto > ap[i]to and magnet > mag[i]net. The bidirectional character of this phonological phenomenon has been verified by authors of the area (FLEGE, 1995; PAVLENKO, 2000; COOK, 2002; 2003; KECSKES, 2008; LIMA, 2012; GHAWES, 2017), who identified that the phonological categories of L1, even if they are already structured in the bilingual speaker's mind, they could change from the interference caused by the acquisition of L2. For this, we used a variationist methodology (LABOV, 1975; LABOV, 2008 [1972]), which was attended by 39 informants: 18 bilingual Brazilian informants with different levels of proficiency and 21 monolingual informants – 18 monolingual Brazilian informants and 3 monolingual American informants. These informants were asked to read sentences and texts in Portuguese and English with occurrences of the phenomenon, which were recorded, quantified and coded in order to be statistically analyzed using Goldvarb X (SANKOFF, TAGLIAMONTE & SMITH, 2005) and acoustically analyzed using Praat (BOERSMA & WEENINK, 2015). From this process, we performed five rounds (L1 + L2, L1, L2 - Bilingual Brazilians, L1 - Monolingual Brazilians and L1 - Monolingual Americans). Given the results obtained, we found that the application of the phenomenon was not so productive, especially in the data of monolingual informants. We also found that the variables selected as relevant to the occurrence of the phenomenon, both in the perceptual and acoustic analyses, were not so discrepant, leading us to believe that, in both contexts of analysis, the variation of the phenomenon follows a systematic pattern. We conclude, therefore, that the process of L2 acquisition does not occur solely in a unidirectional sense, varying in correlation with linguistic and extralinguistic dimensions, confirming the bidirectional link between L1 and L2.